ENERGY SECURITY OF THE COUNTRY DURING THE WAR: BARRIERS AND PROSPECTS FOR OVERCOMING - KOVALENKO, Yuliia; LAZARENKO, Dmytro; MARCHENKO, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article unveils the stages of evolution of the concept of energy security from the early ХХ century to the present realities, taking into account the full-scale aggression on the territory of Ukraine. The authors emphasize that in the past, energy security was primarily associated with ensuring the supply and delivery of oil and gas, but now it has become complicated with the supply of fuel for military purposes. It is noted that the Russian aggression against Ukraine has underscored the importance of the energy security policies of the United States and European countries. The article analyzes research results revealing security threats associated with the energy sector in the United States. Emphasis is placed on the necessity of decision-making covering technical, political, and programmatic aspects. New strategies for the energy market, including alternative energy sources and high-efficiency technologies, are discussed. The article examines the link between international conflicts and energy security, including the Persian Gulf crisis of 1991 and the Iraq war of 2003. The results of political debates regarding the confrontation between Russia, the United States, and Europe are presented, highlighting the need for the development of alternative energy sources and energy efficiency. It is determined that the future of energy policy should consider global trends and international relations, not just economic and geopolitical aspects. Current trends in the energy sector and their impact on energy security in conflict conditions are discussed. The importance of transitioning to renewable and alternative energy sources is emphasized amid declining reserves of traditional fuels and rising prices. Problems associated with continued dependence on fossil fuels, such as resource depletion, global warming, environmental issues, and geopolitical conflicts, are mentioned. The article underscores the necessity of cooperation between energy-consuming countries’ governments to reorient their energy sectors. The growing threat of global warming and other issues necessitates immediate action to transition to less polluting energy sources. The article analyzes the impact of the war in Ukraine on the region’s energy security and demonstrates the necessity of developing alternative energy sources to ensure energy supply stability. It is noted that energy security is a crucial element of a country’s economic stability and plays a key role in international relations. Efforts by EU member countries to reduce dependence on gas supplies from Russia and effective steps towards developing alternative energy sources are highlighted. However, difficulties in achieving this goal due to inadequate coordination and increasing gas prices in Europe are noted. The necessity of swift and effective measures to ensure energy security amid modern challenges and conflicts is underscored.